Analysis of coffee seed vigor by extractive electrospray ionization mass spectrometry. Issue 8 (8th February 2018) - Zhou, Yalian; Cui, Meng; Yin, Qin; Deng, Min; Hao, Yingbin; Huang, Xueyong; Luo, Liping
Abstract : EESI-MS and multivariate analysis distinguish coffee seeds with different vigor. Abstract : Water extracts of coffee seeds of various ages were analyzed in positive ion mode by extractive electrospray ionization mass spectrometry (EESI-MS) without any sample pretreatment, and the typical metabolites were identified by tandem mass spectrometry. Further assessment using principal component analysis (PCA), cluster analysis (CA), and discriminant analysis (DA) demonstrated that a combination of EESI-MS and multivariate analysis could effectively distinguish coffee seeds with different vigor. In PCA, the first three principal components explained 99.3% of the total variation, and coffee seeds with the same vigor were clustered closely together in CA with an accuracy of 100%. In DA, both the accuracy rate of discrimination of the training samples and the success rate of cross validation analysis were 100%. We concluded that coffee seeds with diverse vigor could be differentiated by EESI-MS coupled with multivariate analysis, providing a novel, sensitive, and rapid measurement of seed vigor in coffee.